Adverse effects of 5α-reductase inhibitors: What do we know, don’t know, and need to know? - Traish, Abdulmaged M.; Melcangi, Roberto Cosimo; Bortolato, Marco; Garcia-Segura, Luis M.; Zitzmann, Michael (Reviews in endocrine & metabolic disorders, 2015)
Steroids are important physiological orchestrators of endocrine as well as peripheral and central nervous system functions. One of the key processes for regulation of these molecules lies in their enzymatic processing by a family of 5α-reductase (5α-Rs) isozymes. By catalyzing a key rate-limiting step in steroidogenesis, this family of enzymes exerts a crucial role not only in the physiological control but also in pathological events. Indeed, both 5α-R inhibition and supplementation of 5α-reduced metabolites are currently used or have been proposed as therapeutic strategies for a wide array of pathological conditions. In particular, the potent 5α-R inhibitors finasteride and dutasteride are used in the treatments of benign prostatic hyperplasia (BPH), as well as in male pattern hair loss (MPHL) known as androgenetic alopecia (AGA). Recent preclinical and clinical findings indicate that 5α-R inhibitors evoke not only beneficial, but also adverse effects. Future studies should investigate the biochemical and physiological mechanisms that underlie the persistence of the adverse sexual side effects to determine why a subset of patients is afflicted with such persistence or irreversible adverse effects. Also a better focus of clinical research is urgently needed to better define those subjects who are likely to be adversely affected by such agents. Furthermore, research on the non-sexual adverse effects such as diabetes, psychosis, depression, and cognitive function are needed to better understand the broad spectrum of the effects these drugs may elicit during their use in treatment of AGA or BPH. In this review, we will summarize the state of art on this topic, overview the key unresolved questions that have emerged on the pharmacological targeting of these enzymes and their products, and highlight the need for further studies to ascertain the severity and duration of the adverse effects of 5α-R inhibitors, as well as their biological underpinnings.